Profil kebutuhan media modifikasi wayang beber dalam pembelajaran berbicara dan pemahaman lintas budaya pemelajar BIPA Tiongkok - Salwa Yumna Soyu; Mochamad Whilky Rizkyanfi; Ida Widia (Universitas Mulawarman, 2026)
This study aims to describe the need for modified wayang beber teaching media in speaking and cross-cultural comprehension learning for beginner-level BIPA learners from China based on the perspectives of learners and teachers. The study uses a qualitative descriptive approach involving eight beginner-level learners from Xi'an International Studies University, China, and three teachers from Indonesia University of Education. Data collection was carried out through literature study, interviews, observation, and questionnaires. Data were analyzed using qualitative descriptive techniques by condensing, presenting data, and drawing conclusions. The study found four dimensions of needs: learners' needs regarding the characteristics of wayang beber media, the needs of wayang beber media in facilitating speaking skills, the needs of wayang beber media in cross-cultural understanding, and teachers' needs regarding the use of wayang beber and folk tales. Data triangulation from both perspectives produced a comprehensive profile of needs, including: presenting the story of Malin Kundang with clear and complex visual designs; integrating speaking and cross-cultural understanding learning through structured discussions on cultural values, comparisons between Indonesian and Chinese cultures, and reflective questions to develop learners' empathy; and comprehensive implementation covering print and digital media, guidelines for teachers and learners, assessment tools aligned with competency standards, and multimedia support materials.